Presence of Immune Evasion Cluster and Molecular Typing of Methicillin-Susceptible Staphylococcus aureus Isolated from Food Handlers - Baptistao, Livia G. [UNESP]; Silva, Nathalia C. C.; Bonsaglia, Erika C. R. [UNESP]; Rossi, Bruna F. [UNESP]; Castilho, Ivana G. [UNESP]; Fernandes Junior, Ary [UNESP]; Rall, Vera L. M. [UNESP] (Int Assoc Food Protection, 2016)
The hands and noses of food handlers colonized by Staphylococcus aureus are an important source of food contamination in restaurants and food processing. Several virulence factors can be carried by mobile elements in strains of S. aureus, including the immune evasion cluster (IEC). This gene cluster improves the capacity of S. aureus to evade the human immune response. Many studies have reported the transmission of strains between animals and humans, such as farm workers that have close contact with livestock. However, there are few studies on the transmission between food and food handlers. The aim of this study was to detect the IEC and the mecA gene in strains isolated from food handlers and to type these strains using the spa typing method. Thirty-five strains of S. aureus isolated from the noses and hands of food handlers in three different kitchens were analyzed for the presence of the mecA gene and IEC and by spa typing. All strains were negative for the mecA gene, and the presence of IEC was observed in 10 (28.6%) strains. Fifteen different spa types were observed, with the most frequent being t127 (42.85%) and t002 (11.42%). Strains from the two most prevalent spa types and a novel spa type were typed by multilocus sequence typing. spa types t127, t002, and t13335 were determined to be multilocus sequence types (ST) ST-30, ST-5, and ST-45, respectively. The food handlers may have been contaminated by these strains of S. aureus through food, which is suggested by the low frequency of IEC and by ST that are observed more commonly in animals
Keywords: Food handlers; Immune evasion cluster; spa typing; t127; t13335